Correlates of HIV treatment adherence self-efficacy among adolescents and young adults living with HIV in southwestern Uganda. - Scholastic Ashaba; Charles Baguma; Patricia Tushemereirwe; Denis Nansera; Samuel Maling; Brian C Zanon; Alexander C Tsai (PLOS Global Public Health)
Adherence to antiretroviral therapy (ART) among adolescents and young adults living with HIV (AYLHIV) in sub-Saharan Africa is sub-optimal compared to younger children and older adults. Adherence self-efficacy is one of the intrapersonal factors most strongly correlated with ART adherence. The role of adherence self-efficacy in ART adherence among AYLHIV is not well studied in Uganda. We enrolled 300 AYLHIV between October and December 2021 from an HIV clinic in southwestern Uganda. We collected information on adherence self-efficacy, HIV stigma, depression, self-management, and social skills. We used linear regression to estimate the association between adherence self-efficacy and the covariates of interest. At multivariable adjustment self-management (b = 0.29, 95% CI 0.23-0.35, p<0.001) and social skills (b = 0.16, 95% CI 0.08-0.24; p<0.001) were statistically significantly associated with adherence self-efficacy. The findings imply that interventions directed at enhancing self-management and social skills in AYLHIV may increase adherence self-efficacy and, potentially, HIV outcomes among AYLHIV.